EFL Students' Perspective In Learning Phonetic Symbols - Kania Anisah; Nursyahrina Lubis; Yani Lubis (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
Phonetic symbols are symbols used to explain how a sound is formed. Phonetic symbols can help students explain the different sounds of various English words. The purpose of this study is to find out students' perspectives on learning phonetic symbols. This research uses descriptive qualitative to find English Foreign Language (EFL) students' perspectives on learning phonetic symbols. Data was collected through a questionnaire created with google form that the writes has calculated and analyzed. The results show that students' perspectives are positive in learning phonetic symbol, and earning phonetic symbols, students feel helped in pronunciation and make it easier for them to distinguish each word that has the same pronunciation. Even though many students agree that learning phonetic symbols is difficult, they also strongly agree that learning phonetic symbols can help them speak English better. With this paper, the writers hope that students are able to apply phonetic symbol learning in English language activities so that English pronunciation becomes better.